Multigenerational Workforce Management in Enhancing Team Collaboration in Creative Industries in Indonesia - Irwan Suryadi (North Press, 2025)
This study explores the role of multigenerational workforce management in enhancing team collaboration within Indonesia's creative industry. With the workforce increasingly composed of diverse generational groups, organizations face challenges in integrating these cohorts effectively. The research focuses on three key management practices—communication strategies, conflict management, and inclusive leadership—and their impact on team collaboration. Using a quantitative approach, a sample of 200 respondents from creative industry companies in Indonesia was surveyed. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings revealed that communication strategies, conflict management, and inclusive leadership all positively and significantly affect team collaboration. The study highlights the importance of tailored management practices to accommodate the distinct needs of different generational groups and provides practical recommendations for fostering a collaborative environment. This research contributes to the growing body of knowledge on workforce management in multigenerational teams, particularly in dynamic sectors like the creative industry.